Electrospun titania nanofibres : synthesis and characterization - Tay, Yi Hong. (2010)
Metal oxide materials have derived considerable attention from scientists in recent years due to their potential in functional device applications. Titanium dioxide, also known as titania, is one example and its versatility in diverse applications such as photocatalyst and lithium ion batteries has been well documented. Specifically, one dimensional titania nanostructures have shown immense promise in these areas and various approaches have been taken to synthesize this form of nanostructure. Electrospinning boasts a combination of simplicity and versatility for such an approach.